The Effect of Price, Company Image on Customer Satisfaction and Its Implications on Customer Loyalty at The Heritage Hotel Salak Bogor: The Effect of Price, Company Image on Customer Satisfaction and Its Implications on Customer Loyalty at The Heritage Hotel Salak Bogor - Ayi Muhiban (Institute of Computer Science (IOCS), 2020)
This study aims to determine the effect of price and corporate image to the satisfaction and its implications for customer loyalty Hotel Salak The Heritage Bogor. The population in this study is the customer pest management, while the sample in this study was 112 respondents using purposive sampling sampling technique. To answer the research problem and research hypothesis testing then used path analysis techniques. Managerial implications of this research is customer trust Hotel Salak The Heritage Bogor. The method of research used in this research is descriptive analysis method with a population of about 155 customers. The data analysis technique used is the technique Correlation Analysis to determine the degree of closeness of the relationship between variables. With research and Path Analysis techniques in order to determine how much influence either directly or indirectly. In oprasionalisasinya used help software SPSS 22. The results showed that the price is in the category Pretty good, Service Performance in the category quite well, the satisfaction is in the good category and loyalty in the category quite well. The results showed that 1) the price effect on satisfaction 2) corporate image influence on satisfaction, 3) the satisfaction effect on loyalty, 4) The price does not affect the customer loyalty, 5) the company's image does not affect the loyalty and 6) Overall, satisfaction is the only constructs that can affect customers. The direct effect of 0379 price to satisfaction. The indirect effect through imagery price of 0.149. The direct effect on satisfaction image for 0092 and does not directly influence the image through a price of 0.149 so that the total effect of 0771. The direct effect of satisfaction on loyalty of 0,816 .. The results show determination coefficient of 77.1% and 22.9% Py?, and partial variable price more dominant effect of the variable image. Obtained the conclusion that the effect of the price of the highest impact. Satisfaction showing determination coefficient of 81.6% and 18.4% Py?, from satisfaction to loyalty variable. The test results showed determination coefficient of 77.1% and 22.9% Py?, and partial variable price more dominant effect of the variable image. Obtained the conclusion that the effect of the price of the highest impact. Satisfaction showing determination coefficient of 81.6% and 18.4% Py?, from satisfaction to loyalty variable. The test results showed determination coefficient of 77.1% and 22.9% Py?, and partial variable price more dominant effect of the variable image. Obtained the conclusion that the effect of the price of the highest impact. Satisfaction showing determination coefficient of 81.6% and 18.4% Py?, from satisfaction to loyalty variable.